Curating the digital space: Structural gate-keeping and boundary work in maternity care - Nicola Mackintosh; Shona Agarwal; Qian (Sarah); Annette Briley; Jane Sandall; Natalie Armstrong (Elsevier, 2022)
Digital health occupies an increasingly important role within the context of managing risk and safety in pregnancy. Women routinely use websites, mobile phone apps and social media platforms to learn about 'normal' pregnancy related changes and potential signs of a complication. This paper shifts attention from women's digital experiences to explore staff responsibilities in relation to women's online practices during pregnancy. We draw on Thomas Gieryn's work as an interpretive aid to enable us to understand how staff protect the boundaries of science in the face of circulating competing epistemic claims within the digital maternal health space. We focus on interview data from midwives and obstetricians exploring technology-in-use, drawn from a mixed methods study conducted in 2019, across three UK NHS Trusts. We found that online health information supplemented 'the clinic', providing an additional layer of support to professionalised, bounded forms of care. However, staff drew on relational and material aspects of being with women to legitimate and distinguish in-person from digital forms of care. Digital resources represented different forms of knowledge and communities. Staff were aware of associated credibility claims linked to these resources and expressed concerns that signposting women to online resources legitimised particular forms of authority and expertise implicit within these networks and tools. Staff were also drawn into reassurance practices and digital caregiving as part of uncertainty absorption. This paper offers nuanced understanding of the implicit boundary work associated with digitally mediated care, and how this links to discourses around 'being with women', responsibility and blame.